TINDAK TUTUR DIREKTIF DALAM NASKAH SANDIWARA RADIO BERJUDUL “KEJLOMPRONG KEJINING JAMAN” - Nanda Nursa Alya (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research examines directive speech acts in a radio drama script titled "Kejlomprong Kejining Jaman". The study analyzes directive speech acts within the framework of speech act theory using a pragmatic approach. The data used in this research consists of utterances between characters that contain directive statements. In the radio drama script "Kejlomprong Kejining Jaman," directive speech acts are expressed using both direct and indirect strategies. Direct strategies involve explicit commands, such as imperative sentences, invitations, and prohibitions. Indirect strategies, on the other hand, convey commands implicitly through statements, declarations of necessity, and questions. Direct speech acts often violate politeness principles and are coercive, leading to a lack of ambiguity and indicating a power imbalance between the speakers. Indirect strategies, however, create ambiguity to maintain politeness and encourage the interlocutor to comply willingly. The analysis results are presented in a descriptive format. This descriptive presentation aims to systematically describe and explain the phenomenon of directive utterances in the dialogue between characters.